Assessing Dietary Pattern and Nutritional Status of Small Millet Consumers in Bengaluru, Karnataka (Indian Journal of Extension Education, 2024)
The study examined the dietary patterns and nutritional status of households during 2020. High-income group among urban households of the population showed more preference towards small millets consumption due to their perceived health benefits, but the population in rural regions had higher per capita consumption of small millets (2.2 kg/capita/month) as compared to urbanites (1.4 kg/capita/month). The research also highlighted that 57 percent of rural households integrated small millets into their cultural practices, whereas about 40 per cent of urban households perceived that consumption of small millets managed to regulate their blood sugar level. Furthermore, the study found that small millets constituted 32 per cent of total energy intake in case of rural households, compared to 20 per cent in urban areas. Notably, 67 per cent of urban households and 80 percent of rural households reported experiencing the health benefits of consuming small millets. With these insights, the study suggests policy measures to include small millets in the Public Distribution System (PDS) and the Mid-Day Meal scheme. Additionally, it stresses upon the importance of disseminating information about the nutritional and health advantages of small millet consumption, aiming to encourage adoption in both rural and urban households.